A Role of Working Class Women in the Industry: Exploring the Impact of Gender Inequality on Working Class Women in the Industrial Sector (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is one of the fastest growing economies of the world. There are several policies adopted by Government of India for the development of infrastructure for the country’s economic development. Construction industry is the key for the success of the globalization of Indian economy .Construction sector is providing employment to 7% of total world employment. As the middle class grew in size and wealth, then their need for domestic workers expanded too. Prior to the Industrial Revolution men are domestic servants in about equal numbers with women. However, after industrialization the statistics change dramatically. Some generalizations can be made about women and work during this time. The entry of women into a specific trade signaled a downgrading of the trade. With industrialization, women still earned one-third to one-half of men's wages. New occupations were added for women over time, but these for the most part were ones previously filled by males, but downgraded in status and pay for women. These jobs included secretaries and typists in businesses, store clerks in the new department stores, and teaching. Increased demarcation in the industrial economy was the strict delineation between men's and women's work.